Marketing of Banana in the Municipality of Igbaras, Iloilo. - Deveza, Joseph Elias Geronimo
The study analyzed the marketing of banana in the municipality of Igbaras, Iloilo. Specifically, it identified the marketing channels and the types of middlemen, described marketing practices, determined gross margin and the net returns received by the banana producers and middlemen; and identified the problems encountered by the banana producers and middlemen. Data came from personal interviews of 105 banana producers from the top ten (10) banana producing barangays in Igbaras and 10 banana middlemen identified., The major banana varieties produced and sold were sab-a and latundan. In 2009, the banana producers sold 96,877 kg to wholesaler-retailers (94 perent) and retailers (6 percent). In terms of location of market, a total of 95,103.87 kg were sold inside of Igbaras and 3.81 percent of banana producers sold 1,773.13 kg of bananas outside of Igbaras. Prices were dependent on the eason, variety and maturity. Bananas fetch higher price during low season (low supply), when they are ripe and of latundan variety. In general, the net farm (NFP) received by banana producers be selling within Igbaras was higher than when selling ouside Igbaras. NFP received by selling latundan was higher than selling sab-a. The highest NFP was received for latundan sold within Igbaras (Php 9.88/kg) followed by latundan sold outside (Php 9.29/kg) of Igbaras and sab-a sold within Igbaras (Php 6.56/kg). The highest gross margin was received by the retailers (Php 4.67/kg for latundan. While the wholesaler-retailers received only Php 4.25/kg. Higher net returns were received by the retailers (Php 3.57/kg) selling latundan. The least nett returns were by the wholesaler-retailers (Php 2.49/kg). There is a wide margin between farmgate price of banana set by retailers. For instance, for altundan during the low supply season, the farm gate price is P 13.81/kg while retailers' price is 26.67/kg. Net return for retailer is 3.5/kg for selling latundan. With many producers selling almost identical products (for latundan and sab-a), the banana producers have no market power to influence price of their bananas. Market power rests on the few banana middlemen. The banana producers may consider organizing themselves into "Small Banana Producers of Igbaras" or into a cooperative. In this way, they can support each other in terms of market information, pricing and marketing of their products.